Guidance Note for Fund Staff on the Treatment and Use of SDR Allocations. (Policy Papers; Policy Paper ;, 2021)
This Note provides guidance for staff on the treatment and use of allocations of Special Drawing Rights (SDRs). It presents a consistent framework for IMF country teams to assess the macroeconomic implications of the SDR allocation at the country level, covering the following areas: -- Statistical and accounting treatment. -- General macroeconomic implications and advice. -- Debt sustainability analysis. -- Transparency and accountability. -- Reserve management. -- Implications for Fund-supported programs.